MAGNETIC RESONANCE IMAGING OF THE SACROILIAC JOINT IN DIFFERENTIAL DIAGNOSIS OF EARLY POLYARTICULAR PSORIATIC AND RHEUMATOID ARTHRITIS (STUDY DATA REMARKA) - Elena Yu Loginova; T V Korotaeva; E L Luchihina; A V Smirnov; A A Glazkov; D E Karateev (Научно-практическая ревматология, 2014)
Diagnosis of lesions of the spine and sacroiliac joints may be helpful in discrimination between early psoriatic arthritis (ePsA) and early rheumatoid arthritis (eRA).Objective. To assess the significance of inflammatory back pain (IBP), HLA-B27, and active sacroiliitis (ASI) confirmed by magnetic resonance imaging (MRI) for differential diagnosis of polyarticular ePsA and eRA.Materials and Methods. The study included 29 patients with ePsA (13 males and 16 females, mean age 36.52 ± 11.27 years, average duration of the disease 13.03 ± 9.77 months) and 25 patients with eRA (7 males and 18 females, mean age 52.68 ± 14.7 years, average duration of the disease 4.0 ± 1.72 months). Presence of IBP (according to the ASAS criteria) and HLA-B27 were assessed (in 27 patients with PsA and in 20 patients with RA); ASI signs were assessed based on the MRI data (bone marrow edema/osteitis). DAS, DAS28, M ± SD, Fisher's exact test, t-test, χ2, the Yule coefficients of association (Q: level from -1 to +1) and Phi were calculated; differences were considered to be statistically significant at p <0.05.Results. In patients with ePsA, ASI was detected by MRI significantly more frequently than in patients with eRA (41.4% and 12% of cases respectively, p < 0.016). No correlation between the presence of ASI and DAS28 was observed in both groups. In the ePsA group, IBP was detected in 17 patients (58.6%); it was long-term in 10 (58.8%) of the patients and episodic – in 7 (41.2%) patients. Back pain with mechanical rhythm was observed in 3 (12%) patients with eRA. HLA-B27 was detected in 9 (33.3%) of 27 patients with ePsA and in 3 (15%) of 20 patients with eRA (p < 0.014). In patients with ePsA, a very high level of association between ASI and IBP (Q = 0.91, Phi = 0.56; p < 0.003) and a high level of association between ASI and HLA-B27 (Q = 0.75, Phi = 0.56; p < 0.039) were detected. MRI showed no association between the presence of HLA-B27 and ASI signs in patients with RA.Conclusions. ASI is detected by MRI significantly more often in patients with ePsA; however, it can also be observed in patients with eRA. In patients with ePsA, ASI is closely associated with IBP and HLA-B27; this fact can be used for differential diagnosis of polyarticular ePsA and eRA. The activity level of peripheral arthritis does not affect detectability of ASI by MRI in patients with ePsA.